Šalutiniai daiktavardiniai 1647 m. Evangelijų sakiniai - Judžentis, Artūras (Baltistica, 2004)
COMPLEMENT CLAUSES IN EWANGELIE POLSKIE Y LITEWSKIE (1647) The article deals with the complex sentences containing complement clauses in Ewangelie polskie y litewskie (1647). Attention is paid to the syntactic structure of these sentences and to the semantic relations between main predicate and complement clause. The Gospels translated by Jaknavičius were carefully compared with those by the anonymous translator, and both were compared with the originals, and with the corresponding sentences in Modern Standard Lithuanian. The conclusion is advanced that there were no semantically empty complementisers in the language of the Gospels investigated. Instead, we find subordinators reflecting different types of semantic relationships between complement and main predicate; similar types of semantic relationships are reflected in adverbial clauses introduced by the same subordinators. Furthermore, we observe some differences in the use of subordinators in Jaknavičius’ translations and the anonymous ones.